ENHANCING READINESS TO CREATE VALUE IN THE SPORTS INDUSTRY THROUGH INTELLECTUAL PROPERTY - Noriya, Wanchalee; Srichaisawat, Paiboon; Samahito, Chananan; Chairatch, Punyada; Sriburi, Suttinee (Academic Journal of Thailand National Sports University, 2024)
This study aims to investigate the situation and obstacles of intellectual property (IP) use in the Thai sports industry, as well as to examine the level of knowledge and readiness, and to enhance the readiness for creating value in the sports industry through IP. The mixed research methodology includes a quantitative survey of 400 respondents in the sports industry using questionnaires as a tool for data collection and analysis using descriptive statistics. For qualitative research, 9 key informants with at least 3 years of experience in intellectual property management or related fields in the sports industry were interviewed. The data analysis was conducted using content analysis. The results of the study found that 1) Most participants in the study demonstrated a low overall level of a general knowledge and understanding of IP use in the sports industry with an average score of 4.01. 2) The readiness of the sports industry to use IP for value creation was moderate ( = 3.34, S.D. = 0.55). 3) The guidelines for enhancing readiness to create value in the sports industry through IP include: (1) Raising awareness among stakeholders in sports industry. (2) Developing an IP consulting center for the sports industry, with a focus on integrating IP services with key sports industry driving agencies. (3) Developing an IP Eco-System to help enhance readiness and create value to the overall Thai sports industry. (4) Promoting collaborative efforts through guidelines or plans to drive the sports industry. (5) Encouraging the private sector to recognize the importance of using IP to drive the sports industry.